PENGGUNAAN APLIKASI E- KATOLIK SEBAGAI SARANA PENGHAYATAN IMAN ORANG MUDA KATOLIK PAROKI ST. FRANSISKUS XAVERIUS GANDUSARI - Renita, Yosefien; Wijaya, Albert I Ketut Deni (Lembaga Penelitian STKIP Widya Yuwana, 2025)
This research aims to analyze the utilization of the Catholic-based application, namely e-Catholic, as a means of spiritual experience for young Catholic individuals in St. Fransiskus Xaverius Gandusari Parish. This research can provide benefits and serve as a source of information on the utilization of the e-Catholic application as a tool for spiritual experience. The data analysis technique used the qualitative research method. There are ten informants in this study, namely the Catholic Youth in St. Fransiskus Xaverius Gandusari Parish, Saint Peter and Paul Parish, Wlingi, Blitar. Informants were selected using purposive sampling techniques, in which the sampling was done by selecting those who are most knowledgeable about the utilization of the e-Catholic application. Data collection was conducted through structured interviews and documentation. The results of this research show that the use of Catholic-based applications, namely the e-Catholic application as a means of deepening faith, can help foster the Catholic faith, especially among the Catholic Youth. E-Catholic application can continue to update and add new features to support the deepening of faith among the Catholic Youth.